Evaluate the Effectiveness of Endoscopic Surgery in the Treatment of Laryngeal Paralysis - ابراهيم, مصطفى; العلوني, فايز; الأعرج, حسن (Latakia University Journal -Medical Sciences Series, 2021)
The laryngoscopic surgery, with its various methods, is used in the surgical management of vocal cord paralysis. The aim of our study is to evaluate the effectiveness in terms of duration of surgery, complications, and improvement of respiratory and phonatory functional outcomes. Patients and methods: 63 patients with Vocal cord paralysis (19 males and 44 females) (UVCP 34, BVCP 29) underwent endoscopic surgery; Results were evaluated during surgery and a month later. Results: Important respiratory improved post-operative, confirming that laryngoscopic surgeries effectively reduced the dyspnea, Objective parameters dealing with voice quality show acceptable outcomes, there is no significant difference between the groups in terms of adhesions; Duration of surgery is lower when using microdebrider. Conclusions: The laryngoscopic surgery of vocal cord paralysis is a safe and effective and it contributes to improving the patient's life after improved respiratory results and acceptable voice results.